Use of Xpert Contributes to Accurate Diagnosis, Timely Initiation, and Rational Use of Anti-TB Treatment Among Childhood Tuberculosis Cases in South Central Ethiopia - Sorsa A; Jerene D; Negash S; Habtamu A (Dove Medical Press, 2020)
Abebe Sorsa,1 Degu Jerene,2 Solomon Negash,2 Ashenafi Habtamu1 1Department of Pediatric and Child Health, Arsi University, College of Health Sciences, Asella, Ethiopia; 2Management Sciences for Health, USAID/Challenge TB Project, Addis Ababa, EthiopiaCorrespondence: Abebe SorsaDepartment of Pediatric and Child Health Arsi University, College of Health Sciences, Asella, EthiopaEmail nathanabebe08@gmail.comBackground: Childhood tuberculosis (TB) was under-prioritized, and only 15% of childhood TB cases are microbiologically confirmed. Hence, most childhood TB diagnoses are made on a clinical basis and prone to over- or under-treatment. Xpert is a rapid method for the diagnosis of childhood TB with high sensitivity.Objective: To assess the use of Xpert for accurate diagnosis, timely initiation, and rational use of anti-TB treatment among childhood TB.Methods: In 2016, the hospital facilitated the installation of the Xpert machine. We reviewed data trends over four consecutive years; two years before the arrival of the machine and two years following the implementation of Xpert. Data were extracted retrospectively from electronically stored databases and medical records and entered to SPSS 21 for analysis.Results: In the pre-intervention period (2014– 2015), 404 cases of children presenting with symptoms or signs suggestive of TB (“presumptive TB”) were evaluated using AFB microscopy. A total of 254 (62.8%) TB diagnoses were made, of which 54 (21.3%) were confirmed by smear AFB while 200 (78.7%) were treated as smear-negative TB cases. The mean waiting time to start anti-TB treatment was 6.95 days [95% CI (3.71– 10.90)]. During the intervention period (2016– 2017), 371 children with presumptive TB were evaluated using Xpert. A total of 199 (53.6%) childhood TB cases were notified, of which 88 (44.2%) were Xpert positive and 111 (55.8%) were treated as Xpert-negative probable TB cases. The tendency to initiate anti-TB treatment for unconfirmed TB cases was reduced by a third. Compared with smear AFB, Xpert improved accuracy of diagnosing pediatric TB cases two-fold. The average waiting time to start anti-TB treatment was 1.33 days [95% CI (0.95– 1.71)]. There was a significant reduction in the waiting time to start anti-TB treatment, with a mean time difference before and during intervention of 5.62 days [95% CI (1.68– 9.56)].Conclusion: Xpert use was associated with a significant increase in the accuracy of identifying confirmed TB cases, reduced unnecessary anti-TB prescription, and shortened the time taken to start TB treatment.Keywords: Xpert, AFB smear, childhood TB, confirmed TB, presumptive TB